Fracture, Fatigue, Failure and Damage Evolution, Volume 8 Proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics - Zehnder, Alan T.; Carroll, Jay.; Hazeli, Kavan; Berke, Ryan B.; Pataky, Garrett; Cavalli, Matthew; Beese, Alison M.; Xia, Shuman; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Fracture, Fatigue, Failure and Damage Evolution, Volume 8 of the Proceedings of the 2016 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the eighth volume of ten from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: In-situ Techniques for Fracture & Fatigue General Topics in Fracture & Fatigue Fracture & Fatigue of Composites Damage, Fracture, Fatigue & Durability Interfacial Effects in Fracture & Fatigue Damage Detection in Fracture & Fatigue.
1 Fatigue Damage Precursor Identification Using Nondestructive Evaluation Coupled with Electron Microscopy -- 2 Experimental Fracture Analysis of Tropical Species Using the Grid Method -- 3 Investigating the Effective Fracture Toughness of Heterogeneous Materials -- 4 Improved Hybrid Specimen for Vibration Bending Fatigue -- 5 Experimental Study of Residual Plastic Strain and Damages Development in Carbon Fiber Composite -- 6 Experimental Investigation of Strength of Curved Beam by Thin Ply Non Crimp Fabric Laminates -- 7 Role of Laminate Thickness on Sequential Dynamic Delamination of Curved [90/0] CFRP Composite Laminates -- 8 Application of eMMC Model to Fracture of Metal Sheets -- 9 Hydrolytic Degradation and its Effect on Mechanical Properties of HFPE II 52 Polyimide Preliminary Results -- 10 Mixed Mode and Mode II Fatigue Crack Growth in Woven Composites -- 11 Characterization of Fatigue Induced Damage Evolution in CFRPs Using DIC -- 12 Damage Characterization for Electronic ComponentsUnder Impact Loading -- 13 Dynamic Mode II Delamination in Through Thickness Reinforced Composites -- 14 Measurement of Bond Line Fracture Toughness in Adhesively Bonded Composite Structures by Nanoindentation -- 15 Experimental and Numerical Investigation of Novel Crack Stopper Concepts for Lightweight Foam Cored Sandwich Structures -- 16 Probabilistic Improvement of Crack Propagation Monitoring by Using Acoustic Emission -- 17 Failure Detection of Temporary Structures with Digital Image Correlation for Construction Safety Applications -- 18 Using Digital Image Correlation to Detect Cracking in Opalinus Shale -- 19 Early Detection Of Damage Mechanisms In Composites During Fatigue Tests -- 20 Implementing Noise Multi Frequency Stimulus and Realtime Analysis with Nonlinear Model Tracking.
Keywords: Mechanics, Applied; Solids; Materials -- Analysis; Solid Mechanics; Characterization and Analytical Technique